DEVELOPING EXPERIENTIAL-BASED TEACHING MATERIALS EXPLORING THE SURROUNDING NATURE IN HIGHER PLANTS SYSTEMATICS - Lestari, Rena; Dahlia, Dahlia; Brahmana, Eti Meirina; Irna, Irna; Hamuna, Risma; Septiyono, Muhammad (Universitas Lancang Kuning, 2025)
Indonesia's biodiversity continues to decline annually. One of the causes is the increase in tourist areas that ignore ecological values, reduce green open spaces, and only focus on economic gain. Learning can utilize local potential with the Natural Exploration model in the surrounding area so that students not only learn about plant diversity from books but also have knowledge and sensitivity to the surrounding environment. In the higher plant systematics course, an outdoor learning model is applied so that learning objectives can be achieved. Based on observations made in the higher plant systematics course, data was obtained that learning has not utilized existing local potential and still refers to textbooks with general material about plants. Furthermore, in the Biology Education Study Program at Pasir Pengaraian University, there is no E-Module based on local plants using the Experiential Natural Exploration (EJAS) model. The purpose of this study is to develop teaching materials for the higher plant systematics course based on EJAS. The method used in this study is development research with the ADDIE model. The results of this study obtained that the e-module based on experiential exploration of the surrounding nature (EJAS) for the higher plant systematics course was overall very suitable for use with an average value of 90.4%.